Application of metallic foam in vehicle structure: A review. (2022) - Sunder Sharma, Shyam; Yadav, Shravan; Joshi, Anurag; Goyal, Ashish; Khatri, Rahul
Abstract: Metallic foam has the unique characteristics and its development cerate wide application in the automotive industry, aerospace industry and biomedical implant. It has high porosity, low relative density, high strength, low thermal conductivity, and high absorbing energy capacity. Absorbing energy capacity has become big attraction for vehicle designer. Automotive industry tries to minimise crash of vehicle during collision. Today environment issue is measure issue for us, so to reduce pollutant gases which are released from the vehicle. Vehicle weight must be less by which consumption of fuel will less and simultaneously efficiency will increase. To tackle the environment issue electric vehicle are coming, for manufacturing the electric vehicle, lightest and strongest material are being required. Metallic foam material consists of all these characteristics. In this paper we have studied the application of metallic foam material in various vehicle structure or automobile and which material has been used in manufacturing of vehicle structure.